An S-scheme α-Fe2O3/Cu2O photocatalyst for an enhanced primary amine oxidative coupling reaction under visible light. Issue 27 (1st July 2022) - Li, Zhen; Ye, Shan; Qiu, Ping; Liao, Xiaoyuan; Yao, Yue; Zhang, Jingzhao; Jiang, Yan; Lu, Shuxiang
Abstract : Photoredox catalysis under visible light has been recorded as a potential and reassuring recipe for organic synthesis. Abstract : Photoredox catalysis under visible light has been recorded as a potential and reassuring recipe for organic synthesis. More and more heterojunction catalysts have appeared in people's fields of vision, especially those with S-scheme heterojunction structures. The S-scheme heterojunction structure of a photocatalyst can remarkably improve its photocatalytic efficiency. Here, an S-scheme α-Fe2 O3 /Cu2 O heterojunction photocatalyst was designed and fabricated for the primary amine oxidative coupling reaction. On account of that, the S-scheme structure effectively separated the photogenerated electron–hole pairs and enhanced the photoredox ability of the photocatalytic system. The α-Fe2 O3 /Cu2 O composite could also enhance the reactivity to a large extent. This work will provide new insight into the design of photocatalysts with a more reasonable structure and higher performance.